(untitled) (The Journal of Research ANGRAU, 2026)
A field experiment was conducted during rabi, 2024-25 on sandy clay loam soils of dryland farm, S.V. Agricultural College, Tirupati, with the objective to find out optimum time of sowing and yield parameters of fodder oat in Southern Agro-Climatic Zone of Andhra Pradesh. The experiment was laid in the randomized block design with factorial concept and replicated thrice.Treatments include three varieties viz., V1: RO-11-1, V2: OS-403 and V3: OS-6 with five sowing windows viz., S1: October I FN, S2: October II FN, S3: November I FN, S4: November II FN and S5: December I FN.The results showed that the significantly higher green (18104 kg ha-1) and dry fodder yield (4735 kg ha-1) and N, P and K uptake by the crop at harvest (142 kg ha-1, 21.6 kg ha-1 and 138 kg ha-1 respectively) were obtained with RO-11-1 sown during November II FN. The available N, P2O5 and K2O in the soil (208 kg ha-1, 53.6 kg ha-1 and 223 kg ha-1 respectively) at harvest recorded higher with OS-403 sown during October I FN compared to all other treatments.